1913 Mich. Pub. Acts 472 - (:unkn) unknown (My University, 1913)
An Act Providing for the Registration of the Purchasers of Guns, Pistols, Other Fire-arms and Silencers for Fire-arms and Providing a Penalty for Violation, § 1-2: Every person, firm or corporation engaged in any way or to any extent in the business of selling at retail guns, pistols, other fire-arms and silencers for fire-arms shall keep a register in which shall be entered the name, age, occupation and residence (if residing in the city with the street number of such residence) of each and every purchaser of such guns, pistols, other fire-arms or silencers for fire-arms together with the number or other mark of identification, if any, on such gun, pistol, other fire-arms or silencer for firearms which said register shall be open to the inspection of all peace officers at all times.
Keywords: REGISTRATION